(Fear of) SARS-CoV-2 infection and psychological distress: a population-based cohort study in southern Switzerland - C. Sculco; B. Bano; G. Piumatti; R. Amati; C. Barbui; L. Crivelli; M. Purgato; E. Albanese (Cambridge University Press, 2024)
Abstract Aims It is widely recognized that the COVID-19 pandemic exerted an impact on the mental health of the general population, but epidemiological evidence is surprisingly sparse. We aimed to explore the association between serologically confirmed SARS-CoV-2 infection and psychological distress - assessed by symptoms of depression, anxiety and stress - in the general adult population in southern Switzerland, a region widely affected by the pandemic. We also investigated whether this association varied over time and between pandemic waves from late 2020 through 2021. Methods We used data from 305 adults who participated in the Corona Immunitas Ticino prospective seroprevalence study in southern Switzerland, including results of the serological tests of SARS-CoV-2 infection collected in June 2021, and explored associations with depression, anxiety and stress scores as measured by the 21-item Depression, Anxiety and Stress Scale at three time points between December 2020 and August 2021, accounting for socio-demographic and health characteristics. Results In our sample, 84.3% of the participants (mean age of 51.30 years, SD = ±.93) were seronegative at baseline. Seropositive (i.e., infected) participants had a decreasing probability of being depressed and anxious through the COVID-19 pandemic waves compared to the seronegative (non-infected) participants. Further, seropositivity at baseline was also associated with more rapid decline in depressive, anxiety and stress symptomatology, and younger age and the presence of chronic diseases were independently associated with mild anxiety (OR = .97; P = 0.013; 95% CI = 0.95, 0.99; OR = 3.47; P = 0.001; 95% CI = 1.71, 7.04) and stress (OR = .96; P = 0.003; 95% CI = .94, .99; OR = 2.56; P = 0.010; 95% CI = 1.25, 5.22). Conclusions Our results suggest that the MH consequences of the pandemic may not be due to the SARS-CoV-2 infection per se, but to fears associated with the risk of infection, and to the pandemic uncertainties.